Study on the Combustibility of Main Tree Species in Mu Us Sandy Land. Issue 1 (September 2021) - Li, Fuguo; Zhao, Xiaobin; Sun, Jingyu; Guo, Jinmei; Wei, Jianheng; Gao, Zhongliang; Cui, Fei; Long, Tengteng
Abstract: The physical and chemical properties of fuels determine forest combustibility, influence forest fire intensity, spread speed and so on. The physical and chemical properties of fuels are influenced by the moisture, ash and calorific of combustibles. It is important to study the combustibility of main arbor in forest for reducing the intensity of forest fire and protecting forest resources. The moisture, caloric, ignition temperature, crude fat and ash of 21 major Mu Us Sandy land species were measured and analyzed, principal component analysis (PCA) was used to comprehensively rank the physical and chemical properties of arbor and shrub. The results can provide scientific basis for the fire resistance of arbor structure in the Mu Us Sandy land, prevent and reduce the frequency of fire in the region, and protect the ecological resources in the sandy land.